Analysis of the effectiveness and safety of rituximab in patients with refractory lupus nephritis: a chart review. Issue 2 (February 2016) - Contis, Anne; Vanquaethem, Helene; Truchetet, Marie-Elise; Couzi, Lionel; Rigothier, Claire; Richez, Christophe; Lazaro, Estibaliz; Duffau, Pierre
Abstract Lupus nephritis is a life-threatening complication of systemic lupus erythematosus. The standard treatment for this condition, including corticosteroids and cyclophosphamide, results in a 70 % remission rate at 12 months, but it is also associated with significant morbidity. Rituximab, a chimeric anti-CD20 antibody, could be useful, given the central role of B cells in the pathogenesis of systemic lupus erythematosus. Case reports and retrospective series have reported that rituximab is effective for refractory lupus nephritis. However, the double-blind, placebo-controlled LUNAR trial failed to meet its end point. We studied clinical, biological, and immunological data on 17 patients who received rituximab as an induction treatment for refractory lupus nephritis at the University Hospital Center of Bordeaux. A complete treatment response was defined as a normal serum creatinine with inactive urinary sediment and 24-h urinary albumin <0.5 g and a partial response (PR) as a >50 % improvement in all of the renal parameters that were abnormal at baseline, with no deterioration in any parameter. Seventeen patients received rituximab as induction treatment for lupus nephritis refractory to standard treatment by cyclophosphamide. After a follow-up of 12 months, complete or partial renal remission was achieved in 53 % patients. Rituximab therapy resulted in a significant improvement in proteinuria and steroid dose tapering in all patients. Rituximab should be considered as a treatment option for refractory lupus glomerulonephritis.